ASSOCIATION OF CEREBRAL OXYGENATION DURING EXERCISE WITH TARGET ORGAN DAMAGE IN HYPERTENSIVE AND NORMOTENSIVE INDIVIDUALS. (June 2022) - Triantafyllou, Georgios; Triantafyllou, Areti; Dipla, Konstantina; Zafeiridis, Alexandros; Koletsos, Nikolaos; Zafeiridis, Andreas; Gkaliagkousi, Eugenia; Douma, Stella
Abstract : Objective: To investigate whether indices of cerebral oxygenation during exercise correlate with subclinical markers of target organ damage (TOD), namely carotid intima-media thickness (cIMT), arterial stiffness, and retinal vessel diameter in newly diagnosed hypertensives and healthy individuals. Design and method: Hypertension was diagnosed using 24-hour ambulatory blood pressure (BP) monitoring. Patients with white coat or masked hypertension were excluded. Cerebral oxygenation was measured continuously during a three-minute isometric hand grip exercise at 30% of maximal voluntary contraction using near infrared spectroscopy. The average response during exercise in oxygenated-hemoglobin (O2Hb), deoxygenated-hemoglobin (HHb), and total-hemoglobin (tHb, reflecting changes in regional blood volume) were examined. CIMT was measured using ultrasound, arterial stiffness was estimated with augmentation index and pulse wave velocity, and retinal vessel diameters were estimated by the central retinal arteriolar (CRAE) and vein (CRVE) equivalent and retinal arteriovenous ratio (AVR). Univariate analyses were performed and partial correlation was used to account for traditional cardiovascular risk factors to identify independent associations between cerebral oxygenation indices and TOD. Results: Fifty-two newly-diagnosed, never treated hypertensives and 41 healthy normotensive individuals with no known medical history of any other disease were included in our study. There were no differences in anthropometric and laboratory variables between groups except for their BP levels, as expected by study design. Mean cIMT was negatively correlated with the average exercise response in cerebral oxygenation (rhoO2Hb = -0.348, pO2Hb = 0.001; rhotHb = -0.253, ptHb = 0.02). Augmentation index was negatively correlated with cerebral-oxygenation during exercise (rhoO2Hb = -0.374, p < 0.001; rhotHb = -0.332, p = 0.02), whereas no significant correlation was observed between pulse wave velocity and cerebral oxygenation indices. In the adjusted analysis, cerebral oxygenation was correlated with central retinal arteriolar diameter (CRAE rO2Hb = 0.233, pO2Hb = 0.043). Conclusions: Our novel findings suggest that indices of cerebral oxygenation during a submaximal physical task are associated with markers of early, subclinical target organ damage, namely increased carotid intima-media thickness, arterial stiffness and retinal arteriolar narrowing in a population of newly diagnosed hypertensive individuals.